Student Social Philosophy: Roles and Responsibilities in Society - Intan Yunita; Nasikhin Nasikhin; Fihris Fihris (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2025)
This article discusses the role and responsibilities of students in society from the perspective of social philosophy. Students are seen as agents of change who have a great moral and intellectual responsibility in shaping a more just and sustainable society. The literature study approach is used to explore social philosophy concepts that are relevant to student participation in society. The results of the analysis show that the use of philosophical thinking as a basis for action by students, such as the concept of social justice according to John Rawls, Mahatma Gandhi's non-violent approach, and Paulo Freire's critical thinking, allows them to become more effective agents of change. Students are also involved in various social and political activities, such as protests, advocacy campaigns, volunteer activities, as well as participation in political movements, as a concrete form of their role as agents of social change. Challenges and obstacles students face, such as unsupportive authority reactions, risks of repression, and internal conflicts, are also discussed. Strategies to increase student roles and responsibilities, such as education and critical awareness, involvement in student organizations, community service programs, collaboration with external parties, and advocacy and social campaigns through social media, are proposed as measures to help students play a more active and effective role in building a more just, democratic, and sustainable society.